The reading-guiding-muraja'ah method as a learning strategy for yellow books in islamic boarding schools in south west aceh - M. Reza Assiffi; Syibran Mulasi; Masni; Riyan Darwis (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study analyzes the application of the (Read, Guide, Muraja'ah) Method in the learning of yellow books in Islamic boarding schools in the Southwest Aceh region as a response to the weakening of students' Arabic language skills, increasing dependence on translated books, and the challenges of modernization that affect the quality of classical text comprehension. Through the Read stage to train phonetic accuracy, the Guidance stage to provide correction and conceptual understanding, and the Muraja'ah stage to strengthen memory, this method is considered capable of improving reading accuracy, understanding of meaning, motivation, and discipline of students. A qualitative descriptive approach is used to explore the learning process in depth. The validation results show that aspects of all three methods are in the